The Role of Islamic Higher Education in Strengthening the Halal Ecosystem in Indonesia - Firdaus, Dwi Hidayatul; Ma’arif, A. Samsul; Rouf, Abd. (Pustaka Peradaban, 2025)
This study examines the role of Islamic tertiary institutions in strengthening the halal ecosystem in Indonesia through the establishment and operation of Halal Centers. These centers, acting as Halal Inspection Agencies (LPHs), are expected to significantly impact halalization efforts by integrating scientific knowledge with Islamic values, ultimately serving as hubs for halal studies. Through qualitative research on Halal Centers at five State Islamic Higher Education Institutions (PTKIN), this study analyzes the individual contributions of each institution to generalize their collective role. The findings reveal that these institutions make significant contributions to the advancement of halal potential in Indonesia through three key roles: (a) developing human resources through the establishment and operationalization of Halal Centers; (b) increasing access to halal certification by functioning as LPHs, thereby incentivizing wider adoption of halal standards among businesses; and (c) promoting halal product research and business incubation, particularly for Micro, Small, and Medium Enterprises (MSMEs). These universities, leveraging their infrastructure, human resources, and expertise, are positioned to pioneer innovation and research within the halal sector. Furthermore, practical initiatives undertaken by these institutions include disseminating information on halal certification to MSME stakeholders and assisting with Halal Product Process (PPH) implementation.